Determinan Personal Hygiene Pada Anak Usia 9–12 Tahun - Andiko Nugraha Kusuma (Universitas Faletehan, 2019)
Primary school-age children are good growth periods, children need to be monitored for their health. Personal hygiene is very important for children because the child is affected by the disease because of bad in personal hygiene. The purposes of this research is to find the factors associated with personal hygiene of 9-12 years old children in Kalanganyar Village, Puskesmas Pancur in 2018. The design of this research is cross sectional. The population of this research is all children in 9-12 years who living in Kalanganyar Village with a sample of 73 respondents that has been taken using total sampling. Primary data collection using questionnaire and interview method. Data analysis was done univariat and bivariate. The result obtained 30,1% less good in personal hygiene, 38,4% have lack of knowledge, 42,5% have a negative attitude, and 72,6% are not exposed to social media access. The result of analysis showed there was no significant correlation between knowledge and personal hygiene (p=0,623), there was significant correlation between attitude (p=0,032) and social media access (p=0,044) with personal hygiene of 9-12 years children in Kalanganyar Village. The suggestion of this research is are children adopting a good clean and healthy lifestyle and repeating it continuously, and practicing good examples of good health and life behaviors with complete and orderly stages.